2013
DOI: 10.1007/s10459-013-9444-x
|View full text |Cite
|
Sign up to set email alerts
|

An argument-based approach to the validation of UHTRUST: can we measure how recent graduates can be trusted with unfamiliar tasks?

Abstract: There is a need for valid methods to assess the readiness for clinical practice of medical graduates. This study evaluates the validity of Utrecht Hamburg Trainee Responsibility for Unfamiliar Situations Test (UHTRUST), an authentic simulation procedure to assess whether medical trainees are ready to be entrusted with unfamiliar clinical tasks near the highest level of Miller's pyramid. This assessment, in which candidates were judged by clinicians, nurses and standardized patients, addresses the question: can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 38 publications
2
58
0
1
Order By: Relevance
“…Even though it has been shown for mini-CEX that rater training had no effect on the reliability of the exam scores [30] it is an unconditional requirement to reach solid reliability for the assessment of competences [11]. Another study also showed that rater training had a positive effect on the quality of inferences made by raters in competence modeling [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though it has been shown for mini-CEX that rater training had no effect on the reliability of the exam scores [30] it is an unconditional requirement to reach solid reliability for the assessment of competences [11]. Another study also showed that rater training had a positive effect on the quality of inferences made by raters in competence modeling [31].…”
Section: Discussionmentioning
confidence: 99%
“…Design of the 360-degree competence-based assessment This 360-degree assessment for undergraduate medical students close to their graduation was based on the top 10 competencies identified by Fürstenberg et al [17] and comprised an authentic simulation for medical students in the role of a beginning resident on a busy first day in hospital developed earlier [11]. The assessment includes five phases, which can be completed by 30 participants per day, six groups of five students each (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, a tool aligned to the construct of competency progression would incorporate an expert's perception of the trainee's increasing clinical ability. 23 Entrustability scales are a species of construct-aligned anchor scales because they align with the expertise and priorities of clinician-educators. The Zwisch scale, 24 a behaviorally anchored ordinal (1-4) scale used to grade the degree of guidance necessary during a technical procedure, is a great simple example.…”
Section: Entrustability Scales: a Species Of Construct-aligned Scalesmentioning
confidence: 99%